Managing Chronic Urticaria: Quo Vadis? - Elena Petkova; Maria Staevska (European Medical Journal, 2020)
Chronic urticaria (CU) is one of the most commonly diagnosed skin conditions. CU is characterised by the presence of recurrent wheals and/or angioedema and intense pruritus persisting for at least 6 weeks. Subtypes of CU include chronic spontaneous urticaria and chronic inducible urticaria. Following diagnosis, adequate trigger identification and appropriate treatment can significantly reduce disease activity and improve the patient's quality of life and disease outcomes. Current guidelines recommend a stepwise approach in the management of CU, including non-sedating oral antihistamines, administered in up to four times the conventional dose, the monoclonal antibody omalizumab (anti-IgE), and eventually cyclosporine as an add-on therapy for patients with antihistamine-refractory CU. Potential disease-related biomarkers are needed to predict the therapeutic response that would lead to establishment of personalised regimens and treatment plans. This paper reviews the current perspectives and guidelines for classification, diagnosis, and management of CU.